Optimum model for prediction of Daughters Pregnancy Rate in crossbred cattle of Kerala, India: prediction of Daughters Pregnancy Rate in crossbred cattle of Kerala - SADAN, TINA; Valsalan, Jamuna; Kulangara, Anilkumar; Venkatachalapthy, Thirupathy (Indian Journal of Dairy Science, 2024)
To improve the overall performances of dairy cattle, fertility should be given due weightage along with milk yield in breeding programmes. The study was initiated to genetic evaluate the crossbred cattle of Kerala based on fertility traits especially Daughters Pregnancy Rate (DPR). An optimum model for the prediction of DPR based on  standardized Voluntary Waiting Period (VWP) has been developed. Data pertaining to 1180 crossbred cattle sired by 208 Frieswal bulls, spread over a period of 17 years from 2003 to 2020, maintained at different farms of Kerala Veterinary and Animal Sciences University and field centres of ICAR- Filed Progeny Testing Scheme were analysed in the study. VWP is standardized as 55 days as cattle inseminated during 55 -63 days after calving  had highest milk yield and  pregnancy rate. Average DPR in the study was estimated as 0.34 ± 0.01 with coefficient of variation 74.61%. Seven simple and multiple regression models were developed using all possible combinations of Age at First Calving (AFC), Service Period (SP) and milk yield per day of lactation (MY/LL) for the prediction of DPR. It was observed that model containing only SP as independent variable fulfilled four criteria’s viz. highest R2,  minimum mean sum of squares due to error (MSSe), lowest Aaike information criterion (AIC),  Bayesian information criterion (BIC) values and the optimum model developed was DPR = 0.002(309-SP).The study standardized VWP and developed an optimum model for prediction of DPR in crossbred cattle of Kerala, also emphasis the importance of fertility in genetic evaluation and selection criteria of dairy cattle.